Temperature dependency of hourly precipitation intensities – surface versus cloud layer temperature. (17th February 2016) - Formayer, Herbert; Fritz, Alexandra
ABSTRACT: Possible changes in precipitation intensity, especially for extreme precipitation events, in a warming climate are of great societal concern. It is generally expected that heavy precipitation will become more intense. The relationship between precipitation intensity and temperature and other factors influencing precipitation is not fully understood yet. Still, a robust estimate for a possible increase in precipitation intensity is of great importance for many applications, such as the planning of flood control or adaptations in agricultural systems. The Clausius‐Clapeyron relation, which explains the dependency of the water holding capacity on air temperature, has been proposed as a possible constraint. It would yield an increase of about 7% K −1 warming (deemed the Clausius‐Clapeyron rate). In this article, the relation between heavy 1‐h precipitation and 2‐m air temperature in observations from the recent past at the station in Vienna Austria is studied. Following a methodology outline in previous studies, this study will show that increases around the Clausius‐Clapeyron rate are found with steeper increases towards the warm end. These findings confirm those of comparable studies. It remains unclear whether there is a limit to that scaling at a certain temperature because the results become unreliable at the warm end of the temperature range due to insufficient sample sizes. In a second step, the dependency of hourly precipitation extremes on the mean temperature between the 700 and 500 hPa layers is analysed in the same manner. A similar increase is found, but the results remain robust even in higher percentiles of the distribution of temperature values in the respective data sets.